GEOMETRY TOWER ADVENTURE PADA ANAK USIA DINI DI DESA SUKOREJO KECAMATAN BOJONEGORO - Dian Ratna Puspananda; Anis Umi Khoirutunnisa’; M. Zainudin; Anita Dewi Utami; Nur Rohman (IKIP PGRI Bojonegoro, 2017)
ABSTRACTThe introduction of geometry is considered important since early age because part of form recognition learning. This is one of the earliest concepts that children must master in cognitive development. Children can distinguish objects by shape first before based on other features. By giving the introduction of geometric shapes from an early age means that the child will have a learning experience that will support the learning of mathematics in the next level of education. Community Service Activities under the title Geometry Tower Adventure at Early Childhood in Sukorejo Village Bojonegoro District Bojonegoro District aims to train children to know the type of shapes, colors, and soft and coarse motor skills by using their preferred game. This PKM activity started on September 11, 2017 until September 16, 2017, followed by all Singajaya Islam Kindergarten students, amounting to 100 students. As the activity progresses the students follow the game path with enthusiasm and joy. In addition we also provide five sets of props in the form of geometry towers and the steps of its use in learning to the school to be utilized in the future.Keywords: Geomerty tower adventure, Early childhoodABSTRAKPengenalan geometri dianggap penting dikenalkan sejak usia dini karena bagian dari pembelajaran pengenalan bentuk. Hal iniÂ merupakan salah satu dari konsep paling awal yang harus dikuasai oleh anak dalam pengembangan kognitif. Anak dapat membedakan benda berdasarkan bentuk terlebih dahulu sebelum berdasarkan ciri-ciri lainnya. Dengan memberikan pengenalan bentuk geometri sejak usia dini berarti anak mendapatkan pengalaman belajar yang akan menunjang untuk pembelajaran matematika di tingkat pendidikan selanjutnya. Kegiatan Pengabdian kepada Masyarakat dengan judul Geometry Tower Adventure pada Anak Usia Dini di Desa Sukorejo Kecamatan Bojonegoro Kabupaten Bojonegoro bertujuan melatih anak untuk mengetahui jenis bentuk, warna, serta melatih motorik halus dan kasar dengan menggunakan permainan yang disukai mereka. Kegiatan PKM ini dimulai pada tanggal 11 September 2017 sampai dengan 16 September 2017, diikuti oleh seluruh siswa TK Islam Singajaya yang berjumlah 100 siswa. Saat kegiatan berlangsung siswa mengikuti alur permainan dengan antusias dan gembira. Selain itu kami juga memberikan lima set alat peraga berupa menara geometri serta langkah-langkah penggunaanya dalam pembelajaran kepada pihak sekolah agar bisa dimanfaatkan dikemudian hari.Kata Kunci: Geomerty tower adventure, Usia dini